Cardiac rehabilitation patient perspectives during COVID-19 pandemic: quantitative and qualitative study - Jug, Borut; Sedlar Kobe, Natasa; Stojinic, Dejana; Lainscak, Mitja; Farkas, Jerneja (Frontiers in Cardiovascular Medicine, 2024)
Background This study aimed to quantitatively assess stress, anxiety and obsessive thinking related to coronavirus disease-19 (COVID-19) and qualitatively appraise perceptions in patients after acute myocardial infarction (AMI) undergoing cardiac rehabilitation (CR) during the COVID-19 pandemic. Methods We used mixed-methods design in patients referred for CR in 2 centres which delivered uninterrupted service during COVID-19 pandemic. Coronavirus Anxiety Scale (CAS), Obsession with COVID-19 Scale (OCS), COVID-19 Stress Scale (CSS), Hospital Anxiety and Depression Scale (HADS), and in-person interviews (combination of a priori questions and probing) were used to evaluate patient experience and perceptions with COVID-19 and the healthcare services during pandemic. Results In total, 109 patients (mean age 59 ± 10, 20% women) were included in quantitative part and in 30 of them we conducted the in-person interviews. About a quarter of patients met HADS threshold for anxiety and depression while CAS and OCS results demonstrated extremely low possibility of coronavirus related dysfunctional thinking (3%) and anxiety (2%). The CSS indicated the most prevalent concerns were related to COVID-19 vaccines safety (60%) and fear of getting infected (60%). During interviews, patients perceived the CR as well as health care providers as safe, trustworthy and with enough support to avoid or manage COVID-19 related health risks. Conclusions Overall, patients reported AMI affected their lives more than the COVID-19 pandemic. The COVID-19 related stress and anxiety were relatively low and mostly related to general views of infectious disease. CR was perceived safe and trustworthy in terms of primary disease and COVID-19. Lay summary This mixed-method study included 109 patients with acute myocardial infarction who underwent cardiac rehabilitation during the COVID-19 and focused on their experience and perceptions with COVID-19 and the healthcare services during pandemic. - Patients reported acute myocardial infarction affected their lives more than the COVID-19 pandemic. - The COVID-19 related concerns were mostly related to general views of infectious disease (vaccine safety, fear of getting infected) whilst cardiac rehabilitation was perceived safe and trustworthy environment during COVID-19.